Hypopigmented mycosis fungoides: An immunological investigation of tumor-infiltrating T cells - Mei Nasu-Tababuchi; Taku Fujimura; Aya Kakizaki; Kosuke Shido; Naokazu Hatchome; Yoshiyuki Kusakari; Setsuya Aiba (Wolters Kluwer Medknow Publications, 2016)
Hypopigmented mycosis fungoides (HMF) is a clinical variant of MF presenting a good prognosis. In this report, we describe a case of HMF with dense infiltration of tumor-infiltrating leukocytes that bear several cytotoxic molecules, such as granulysin and T-cell intracellular antigen-1. In addition, our immunohistochemical study revealed that the ratio of Foxp3+ regulatory T cells to the total CD4+ cells is decreased in the lesional skin of HMF, compared with that of conventional MF. Our case suggested possible mechanisms for the hypopigmentation and good prognosis of this type of MF.